Temperature dependence of the electrical resistivity in amorphous metallic alloys. - Al-Qadi, Khalid. (University of Ottawa (Canada), 2001)
The purpose of this study is to investigate the conduction electrons' interaction mechanisms over the wide temperature range in order to find possible deviations from the existing theories. The temperature dependence of the electrical resistivity of two scattering systems, the crystalline and the amorphous, in the range of 1.7--300 K is studied. In the pure crystalline metals, the nearly-free-electron model can qualitatively and quantitatively account for the temperature dependence of the electrical resistivity. In the low-temperature range, the electron-electron scattering is the dominant scattering mechanism. Above the Debye temperature, the phonon-electron scattering is the dominant scattering mechanism. The temperature dependence of the electrical resistivity for the amorphous metallic alloys can be described qualitatively by the Ziman model. The scattering mechanism of the conduction electrons of the samples can be categorized in the weak scattering limit regime. A small, but significant correction must be added to the Ziman model in order to account for the additional scattering contributions that exist in the wide temperature range. In the very-low-temperature range the electron-electron interaction effect is the major correction to the temperature dependence of the electrical resistivity. In the low-temperature range, the weak localization effect is the major correction to the temperature dependence of the electrical resistivity. In the high-temperature range, the temperature dependence of the electrical resistivity is linear with a small but significant correction. For some samples the magnetic contribution is the major correction, for others the multiphonon scattering is the major correction. For the resistivity minima at temperatures below 20 K could be due to the Kondo effect. A more plausible explanation, however, is the electron-electron interaction effect. The Ziman model with the proper corrections is found to be an adequate and successful model in accounting for the temperature dependence of the electrical resistivity of all of the studied amorphous metallic alloys.
Keywords: Physics, Electricity and Magnetism.